Wan Azizah continues Anwar's hindered agenda in Kajang - New Sabah Times English, (KK) (New Sabah Times English (KK), 2014)
KUALA LUMPUR: The selection of Parti Keadilan Rakyat (PKR) president Datin Seri Wan Azizah Wan Ismail (pictured) as the party's candidate for the byelection for the Kajang State Legislative Assembly seat is seen by political analysts as an effort to continue the political agenda of her husband that was hindered.